Spillovers to Ireland - Kanda, Daniel (IMF Working Papers; Working Paper ;, 2008)
This paper discusses Ireland's trade and financial linkages with key partner countries, and uses a vector autoregression to examine the impact of shocks to partner country GDP and shocks to Irish competitiveness on Irish GDP. Two main findings are that shocks to U.S. GDP have a larger impact on Irish GDP than shocks to the euro area or the U.K. Also, the share of the variance of Irish GDP explained by shocks to competitiveness rises with the forecast horizon, suggesting that past erosion of competitiveness may yet have a more substantial impact on economic activity.